BUSINESS ETHICS AND EFFECTIVE SPEECHES COMMUNICATION OF THE EDUCATIONAL PRIMARY SCHOOL - Иовхимчук, Наталья (SWorldJournal, 2020)
The article deals with the formation of business etiquette and effective speech communication in elementary school teacher. The study reveals recommendations for effective communication in society and reflects the communicative traditions of a particular